Injectable platelet‐rich fibrin and microneedling for gingival augmentation in thin periodontal phenotype: A randomized controlled clinical trial. (11th February 2020) - Ozsagir, Zeliha Betul; Saglam, Ebru; Sen Yilmaz, Berza; Choukroun, Joseph; Tunali, Mustafa
Abstract: Aim: The aim of this present study was to evaluate the effect of gingival thickness (GT) and keratinized tissue width (KTW) using injectable platelet‐rich fibrin (i‐PRF) alone and with microneedling (MN) in individuals with thin periodontal phenotypes. Materials and Methods: In this split‐mouth study, 33 systemically healthy patients with thin periodontal phenotypes were randomly treated with MN + i‐PRF and i‐PRF. I‐PRF was injected on one side, and MN + i‐PRF was performed on the other side of the same patient at 4 sessions with 10‐day intervals. Clinical periodontal measurements, GT and KTW were assessed before the treatment and every month for six months after the final injection. Results: After the evaluation of GT between the groups, a statistically significant difference was found in MN + i‐PRF group at the sixth month. In the intra‐group comparisons, a statistically significant increase in GT was observed within both i‐PRF [from 0.43 mm ± 0.14 to 0.62 mm ± 0.11 ( p  < .001)] and MN + i‐PRF [from 0.4 mm ± 0.14 to 0.66 mm ± 0.12 ( p  < .001)] groups at the sixth month. Conclusions: In individuals with thin periodontal phenotypes, standalone i‐PRF and i‐PRF with MN may have an influence in increasing GT. The results suggest that application of i‐PRF and MN may be a first step of non‐surgical method for increasing gingival thickness.